Perfluorocarbon droplets in the anterior chamber – Case Report - Nazzal, Rashed Mustafa; Siedlecka, Dagna; Pietras-Baczewska, Agata; Nowomiejska, Katarzyna; Rejdak, Robert (Journal of Education, Health and Sport, 2019)
Perfluorocarbonated liquids (PFCL) are occasionally used in vitreoretinal surgery. In this article, we present a case of a young man who sustained a trauma to his eye resulting in a traumatic cataract and retinal detachment. He underwent combined cataract extraction, intraocular lens implantation and a vitrectomy for retinal detachment. Perfluorodecaline was used to stabilize the retina during the surgery. One day after surgery he was found to have many small bubbles of perfluorodecaline settling in the lower half of the anterior chamber. He was managed conservatively and followed up for a period of 1 year during which there were no sequel for the retained PFCL.